Being an assistant to a shaman - Tanka Subba (Ateliers d'Anthropologie)
This article is built around the author’s experience as a shaman’s assistant. This autobiographical account touches upon the poverty, beliefs in ghosts, and shamanistic practices in a Limbu hamlet of Kalimpong, which is a piece of land between Sikkim and Bhutan. Starting with a brief discussion on who a shaman is, the author describes the situation under which he became an assistant to a shaman whom he had to fetch to deal with the sickness of his brother. The author also brings out the issue of the shaman, or phedaṅgmā in the Limbu language, becoming rare because one could not become one by wishing so or by undergoing training under a senior shaman. He says that to become a shaman is a destiny and the signs of becoming one start to show quite early in childhood in the form of abnormal behaviour in specific cycles of months and on partaking of certain foods. In the end, the author shows concern for the future of shamanism, as it seems to be losing out to organised religions like Hinduism, Buddhism, and Christianity.